Natural Resource Rent and Bank Stability in the MENA Region: Does Institutional Quality Matter? - Abdelaziz Hakimi; Hichem Saidi; Mohamed Ali Khemiri (Risks, 2025)
In natural resource-dependent economies, global resource price volatility makes financial systems more vulnerable to economic shocks. The relationship between natural resource rent and bank stability lies in how fluctuations in resource revenues can affect financial institutions’ stability. The purpose of this paper is twofold. First, it explores the effect of natural resource rent (NRR) on bank stability (BS) in the Middle East and North Africa (MENA) region. Second, it examines whether institutional quality (IQ) moderates the association between BS and NRR. To achieve these goals, we used a sample of 68 conventional banks located in the MENA region between 2005 and 2020 and performed the System Generalized Method of Moments (SGMM) as an econometric approach. The empirical findings show that NRR is negatively and significantly associated with BS, while IQ significantly enhances BS in the MENA region. Additionally, the outcomes support evidence that the MENA banks benefit from an interaction between IQ and NRR. This result was confirmed for both the Z-ROA and Z-ROE as measures of BS. The results of this paper could have several useful applications for policymakers and bankers. Policymakers should prioritize strengthening institutional frameworks to mitigate the adverse effects of resource dependence on financial stability. In addition, bankers are invited to focus on improving institutional quality by fostering an institutional environment, including compliance with anti-corruption standards and coordination with regulatory bodies to boost financial resilience.